Inflation convergence and the determinant factors: A case study on 31 provinces in Indonesia - Rifdah Silfanah Mukhlish; Diah Wahyuningsih (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
This study aims to estimate (the possibility) the inflation convergence among regionals in Indonesia and also analyze the determinant/source factor of the regional inflation. The population of this study consists of 31 provinces by using secondary data of the 2008-2017 period. Consumer Price Index becomes the dependent variable while Gross Regional Domestic Product, Provincial Minimum Wage, credit and Open Unemployment Level become the independent variable. This research uses panel data analysis and Fixed Effect Model regression estimation approach. The result showed that inflation convergence happened among regionals in Indonesia that can be seen through the X1 variable coefficient value of -0.635457 since the value of β < 0. While for the convergence speed calculation, the measurement result showed that the duration needed by the inflation to return to the initial balance or its natural value is 68 months. The study result also showed that Gross Regional Domestic Product, Provincial Minimum Wage, credit and Open Unemployment Level have significant influence on the Indonesia’s regional Inflation in 2008-2017.